Eficacia de Extractos botánicos en el Control del Minador (Liriomyza spp.) en el Cultivo de Gypsophila (Gypsophila paniculata) en el Cantón Cayambe, Provincia de Pichincha - Maurisaca Lema, Fanny Mercedes (2017)
SUMARY The present study was performed to examine the efficacy of botanical extracts in the leafminer in growing gypsophila in Canton Cayambe, Pichincha Province by using botanical extracts compared with chemical control. Completely a block was used for random screening and 9 treatments with three replicates for a total of 27 experimental units. The total area of the assay was 3299 m2 with a gross area of 3288 m2, the area of each experimental block equal to a partial 122.2 m2 gross area of 121.8 m2 with a distance between roads and experimental areas of 0.40 m. The extract from the combination of cinnamon, lemongrass and mint is the one with better efficiency in the leafminer larva followed by chemical rotation of the estate, cinnamon extract has the best severity with respect to adult leafminer followed by the extract mint and chemical farm respectively, corresponding to the heights when cut, there is no statistical significance in the green weight where citronella extract cinnamon and mint is the best in the weight blank cinnamon change is gaining more weight and with respect to the vase life citronella extract cinnamon mint are equal to chemical farm and citronella and peppermint extract. Regarding performance, treatment of the block with cinnamon and citronella extract mint performs better chemical followed by rotation.